Pentingnya Kerja Sama Tim Untuk Meningkatkan Produktivitas Kerja Pada Perusahaan Di Bank Syariah Indonesia Kc Medan Adam Malik - Zulaiha Hasibuan; Muhammad Ikhsan Harahap (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
One of the important things that must be considered in the company is teamwork within the company. It must be seen what kind of teamwork should be applied and what kind of teamwork is happening within the company. The purpose of this research is whether the good or bad teamwork that exists in the company will affect the ups and downs of work productivity in the company. Because basically every company has the same main goal, especially Bank Syariah Indonesia KC Medan Adam Malik, which is to get the maximum profit. And this can be realized by increasing the company's work productivity. The research method in this article is a qualitative method, using a descriptive qualitative approach. With the result that the establishment of good teamwork it will affect work productivity in the company. So it can be concluded that teamwork has a significant positive effect on increasing work productivity in companies at Bank Syariah Indonesia KC Medan Adam Malik.